Analysis of Stress Drop Variations in Fault and Subduction Zones of Maluku and Halmahera Earthquakes in 2019 - Rahmat Setyo Yuliatmoko; Telly Kurniawan (Universitas Negeri Surabaya, 2019)
The amount of stress released by an earthquake can be calculated with a stress drop, the stress ratio before and after an earthquake where the stress accumulated in a fault or a subduction zone is immediately released during an earthquake. The purpose of this research is to calculate the amount of stress drop in faults and subduction in Maluku and Halmahera and their variations and relate them to the geological conditions in the area so that the tectonic characteristics in the area can be identified. This research employed mathematical analysis and the Nelder Mead Simplex nonlinear inversion methods. The results show that Maluku and Halmahera are the area with complex tectonic conditions and large earthquake impacts. The Maluku sea earthquake generated a stress drop of 0.81 MPa with a reverse fault mechanism in the zone of subduction, while for the Halmahera earthquake the stress drop value was 52.72 MPa, a typical strike-slip mechanism in the fault zone. It can be concluded that there is a difference in the stress drop between the subduction and fault zones; the stress drop in the fault was greater than that in the subduction zone due to different rock structure and faulting mechanisms as well as differences in the move slip rate that plays a role in the process of holding out the stress on a rock. This information is very important to know the amount of pressure released from the earthquake which has a very large impact as part of disaster mitigation measures.